A study of acute coronary syndrome in post-menopausal women - Nandyal, Sharanabasappa; Indikar, Mudassir; ., Sangappa (International Journal of Advances in Medicine, 2020)
Background: Ischemic heart disease (IHD) is the most common, serious, chronic, life-threatening illness. Account for around half of the global burden from these conditions, i.e. around 17.9 million lives each year, 2020 WHO. Although many factors can influence an individual’s risk for coronary artery disease (CAD), some factors are unique to women, including reproductive status. Menopause is associated with significant elevations in serum cholesterol levels and a threefold increase in risk of CAD. It has been suggested that these changes result from a reduction in the level of estrogen. One in every two women will die of heart disease and stroke, compared with only 1 in 28 who will die of breast cancer. Contrary to the belief that CAD is a man’s disease. So, this study was undertaken to study the risk factors, clinical profile and Complications (in hospital) of Acute coronary syndrome in post-menopausal women. Methods: An observational study conducted in 100 patients with post-menopausal women admitted in Basaveshwar hospital, Kalaburgi, for a period of 6 months. Study subjects selected after applying inclusion and exclusion criteria. Results: 100 post-menopausal women, 80% were above 50 years, mean age was 59.05 years (±9.97 years). The following risk factors were noted, Hypertension (52%), diabetes (36%), obesity (20%), dyslipidaemia (10%), family history of IHD. Chest pain was the most common presenting complaint in 92%. 39% of the patients were admitted after 12 hours of onset of chest pain. Conclusion: Acute myocardial infarction (MI) is common in post-menopausal women and they generally present late. Because of the late presentation, the beneficial effects of thrombolytic therapy are denied.